TREM2 and microglial immunity in Alzheimer’s disease: mechanisms, genetics, and therapeutic opportunities - Wang, Tianqing; Liu, Xinru; Wang, Xifeng; Hua, Fuzhou; Yan, Lei (Frontiers in Immunology, 2026)
Alzheimer’s disease (AD) is increasingly recognized as a disorder of innate immune dysregulation within the central nervous system. The triggering receptor expressed on myeloid cells 2 (TREM2), a microglial immunoreceptor, has emerged as a pivotal genetic risk factor for late-onset AD, underscoring the critical role of neuroimmune interactions in disease pathogenesis. This review synthesizes recent advances concerning TREM2’s modulation of core microglial functions, including phagocytosis, inflammatory signaling, cellular metabolism, and survival, processes that are essential for responding to amyloid-β plaques and neuronal damage. We highlight the TREM2-APOE pathway as a central mechanism driving the disease-associated microglia (DAM) phenotype and examine how loss-of-function mutations such as R47H disrupt immune surveillance, aggravate amyloid pathology, and promote neuroinflammation. Additionally, we explore the diagnostic and therapeutic potential of soluble TREM2 (sTREM2) and TREM2-targeted immunotherapies, which enhance plaque encapsulation and cognitive outcomes in preclinical models. By integrating genetic, molecular, and clinical evidence, this review establishes TREM2 as a keystone regulator linking amyloidosis, tauopathy, and neuroinflammation, highlighting its promise as a target for disease-modifying therapies.